Anti-gender politics in East-Central Europe: Right-wing defiance to West-Eurocentrism - Kováts, Eszter (My University, 2021)
Anti-gender actors in East-Central Europe (ECE) too claim that gender is an ideological colonization. In this article, in contrasting these accusations with actually existing power relations of the global and European gender architecture, I discuss whether they are – at least to some extent – based on social realities. Neither anti-gender campaigns nor the rise of illiberal forces are ECE phenomena per se and should not be treated as such. However, the relevance of the geopolitical embeddedness of gender equality policies, of gender studies and of feminist and LGBT politics needs to be analysed thoroughly in order to better understand the right-wing discourse. This paper offers a theoretical explanation, based on existing empirical studies and critical theoretical literature. Focussing on the four Visegrád countries, Poland, Czech Republic, Slovakia and Hungary, it attempts to demonstrate the specific drivers of the anti-gender mobilization in this region and argues that anti-gender discourse is a right-wing language of resistance against existing material and symbolic East-West inequalities in Europe.
Keywords: Antifeminismus; anti-gender; East-Central Europe; Europeanisation; feminism; LGBT; Politik; right-wing populism; ddc:320